Idiopathic Pulmonary Fibrosis Is Associated with Common Genetic Variants and Limited Rare Variants - Peljto, Anna L; Blumhagen, Rachel Z; Walts, Avram D; Cardwell, Jonathan; Powers, Julia; Corte, Tamera J; Dickinson, Joanne L; Glaspole, Ian; Moodley, Yuben P; Vasakova, Martina Koziar; Bendstrup, Elisabeth; Davidsen, Jesper R; et al. (American journal of respiratory and critical care medicine, 2023)
Rationale: Idiopathic pulmonary fibrosis (IPF) is a rare, irreversible, and progressive disease of the lungs. Common genetic variants, in addition to nongenetic factors, have been consistently associated with IPF. Rare variants identified by candidate gene, family-based, and exome studies have also been reported to associate with IPF. However, the extent to which rare variants, genome-wide, may contribute to the risk of IPF remains unknown. Objectives: We used whole-genome sequencing to investigate the role of rare variants, genome-wide, on IPF risk. Methods: As part of the Trans-Omics for Precision Medicine Program, we sequenced 2,180 cases of IPF. Association testing focused on the aggregated effect of rare variants (minor allele frequency ⩽0.01) within genes or regions. We also identified individual rare variants that are influential within genes and estimated the heritability of IPF on the basis of rare and common variants. Measurements and Main Results: Rare variants in both TERT and RTEL1 were significantly associated with IPF. A single rare variant in each of the TERT and RTEL1 genes was found to consistently influence the aggregated test statistics. There was no significant evidence of association with other previously reported rare variants. The SNP heritability of IPF was estimated to be 32% (SE = 3%). Conclusions: Rare variants within the TERT and RTEL1 genes and well-established common variants have the largest contribution to IPF risk overall. Efforts in risk profiling or the development of therapies for IPF that focus on TERT, RTEL1, common variants, and environmental risk factors are likely to have the largest impact on this complex disease.
Keywords: idiopatická plicní fibróza; lidé; Whole Genome Sequencing; exom; Idiopathic Pulmonary Fibrosis; Humans; Exome; sekvenování celého genomu